(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2022)
The ability of Schiff bases to form complexes with transition metal ions makes them aparticularly significant family of organic molecules.Complexes of nickel(II), copper(II), and zinc(II) with avariety of Schiff base ligands.. The Schiff bases coordinate via the deprotonated phenolic oxygen orazomethine nitrogen atoms, making them bidentate monobasic ligands. Reflux screening was used toexamine ligands and mixed ligand complexes for antibacterial activity. Antimicrobial activity of metalcomplexes is shown to be greater than that of the free ligand.